Microcontroller based standalone PV system for wireless sensor node - Azim, Md. Anwarul; Huda, S.M. Ariful; Mohammad, Hafizal; Amin, Nowshad (2008)
This study integrates the photovoltaic panel power monitoring, the charge controller as well as switching options for remote monitoring applications of any wireless sensor network. To increase the life time of a sensor node, recharge cycle is optimized in such a way that the battery is not charged randomly even though sunlight is available on PV panel, rather it is charged while discharge reaches to a certain predefined limit. Thus, it increases the storage battery life time by reducing the recharge cycle. Here, a powerful PIC microcontroller is used for future enhancement of a complete sensor node solution for environmental monitoring application. However, cost-efficiency can be obtained by selecting optimum hardware for particular device of specific applications with the same methodology described in this paper.